PENENTUAN KOMODITAS PERTANIAN UNGGULAN DI KABUPATEN JEMBER - Firdaus, M.; Paramu, Hadi; Suherman, Suherman; Jusuf, Cholyubi (Jurnal Sosial Ekonomi Pertanian, 2009)
This research was conducted to know growth of food commodity, tobacco and vegetable, at the same time determine pre-eminent agriculture commodity in every district in Jember. This research was  done in Jember by using secondary data of Badan Pusat Statistik (BPS) Jember. Data research cover data agriculture of food commodity, vegetable, and tobacco in all district in Jember. Analyzer the used is supply analysis (trend linear analysis) and Location Quotient ( LQ) analysis. Result of this research indicate that: (1) Crop paddy, cabbage and tobacco of Na Oogst is crop which at most developed by farmers. (2) Crop paddy, eggplant and tobacco of White Burley is pre-eminent crop in Jember. Keyword: commodity, agriculture, pre-eminent